Laboratory screening of three local entomopathogenic fungal isolates against third-instar Spodoptera frugiperda - LILIAN RIZKIE; TJANDRA ANGGRAENI; I NYOMAN PUGEG ARYANTHA; AGUS SUSANTO (Asian Journal of Agriculture, 2026)
Abstract. Rizkie L, Anggraeni T, Aryantha INP, Susanto A. 2026. Laboratory screening of three local entomopathogenic fungal isolates against third-instar Spodoptera frugiperda. Asian J Agric 10: g100181. https://doi.org/10.13057/asianjagric/g100181. The fall armyworm (Spodoptera frugiperda) is an important pest of maize in tropical production systems, including Indonesia. In the field, control of this pest still relies mainly on synthetic insecticides, making the evaluation of local biological control agents necessary. This study tested three local entomopathogenic fungal isolates, morphologically assigned to Beauveria, Metarhizium, and Lecanicillium, against third-instar S. frugiperda larvae at 10⁶-10⁹ conidia mL-¹. Day-7 mortality and sublethal responses were analyzed with generalized linear models, while LT and LC values were estimated by probit analysis. At 10⁹ conidia mL-¹, mortality reached 85.0% for the Beauveria isolate and 90.0% for the Metarhizium isolate, compared with 63.3% for the Lecanicillium isolate. LT₅₀ values at this concentration were 2.75, 2.56, and 5.08 days, respectively. LC estimates outside the tested concentration range were treated as assay-based comparative indices, not as absolute toxicity thresholds. After 48 h of sublethal exposure, relative growth rate, relative consumption rate, and efficiency of conversion of ingested food were reduced, especially in the Beauveria and Metarhizium treatments. Overall, the Beauveria and Metarhizium isolates showed stronger laboratory performance against S. frugiperda larvae than the Lecanicillium isolate. Molecular confirmation and greenhouse or field validation are still required before practical application can be considered.